Ethylene and expansin biosynthesis related genes polymorphism in local apple (Malus domestica Borkh.) cultivars from VIR Collection of plant genetic resources - I. N. Shamshin; A. V. Shlyavas; A. A. Trifonova; K. V. Boris; A. M. Kudryavtsev (Вавиловский журнал генетики и селекции)
At Pushkin and Pavlovsk Laboratories of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) a diverse collec tion of local apple cultivars is maintained. Some of the cultivars are widely used in breeding programs for their ecological plasticity, increased adaptation to abiotic stress and disease resistance, still there have been no large-scale studies of these local cultivars for fruit storage ability. Fruit softening during storage is an important problem for apple production. Retention of desirable firmness after prolonged storage is one of the key requirements for new apple cultivars. Expansin and ethy lene biosynthesis related genes are known to be involved in control of fruit softening in apple, and gene specific molecular markers have been reported. In this study the polymorphism and allelic configuration of ethylene and expansin biosynthesis related genes Md-ACS1, Md-ACO1 and Md-Exp7 involved in control of fruit softening in 87 local apple cultivars from VIR Collection of Plant Genetic Resources were analyzed. PCR markers Md-ACS1, Md-ACO1 and SSR-marker Md-Exp7 were used in the study. The allele frequencies in the collection generally coincided with the data from previous studies. Md-ACS1 allele 2 associated with reduced ethylene production was found only in three local cultivars, while all the studied local cultivars were heterozygous for the Md-ACO1 locus, as well as most modern Russian apple cultivars. Half of the studied local cultivars were heterozygous for Md-Exp7 (198 : 202). Thirteen local cultivars with rare Md-Exp7 alleles (206, 210 and 212) were detected. No association was found between the Md-Exp7 genotype and the cultivars’ maturation time. The obtained results can be used for additional evaluation of the cultivars’ potential for breeding.